THE EFFECT OF KNOWLEDGE COMPETENCE AND SKILLS COMPETENCY ON THE PERFORMANCE AND CAREER DEVELOPMENT OF ADMINISTRATIVE STAFF IN STATE VOCATIONAL SCHOOLS IN BONDOWOSO DISTRICT - Agus Propianto; Iman Suroso; Zainollah (STIE Mandala Jember, 2021)
This study aims to analyze and examine the effect of knowledge competence and skillcompetence on the performance and career development of administrative staff at SMK Negeriin Bondowoso Regency. The type of this research is survey research, namely research usingexplanation (explanatory) or confirmatory (confirmatory) to explain the influence betweenvariables or causal relationship between variables through hypothesis testing. The population inthis study were 63 people. The sampling technique is the census technique, so the number ofsamples used is 63 respondents. The data analysis method used is path analysis. The results ofthis study can be concluded that the competence of knowledge and competence of skills have asignificant effect on the performance of administrative staff. These results also state thatknowledge competence and skill competence have a significant effect on career development ofadministrative staff in State Vocational Schools throughout Bondowoso Regency.Keywords: Knowledge Competence, Skill Competence, Performance, Career Development